Feeding practices in stunting children aged 24-59 months at Sukamukti Community Health Centre Garut Regency - Tetti Solehati; Anne Mayliani Hidayat; Sri Hendrawati (Riset Informasi Kesehatan, 2019)
Stunting is one of the nutritional problems which has become a global concern. Stunting can be caused by various factors, one of which is the inadequacy of feeding practices. This study aims to describe feeding practices in stunting children. This research used a retrospective method. The study was conducted on 50 respondents. The research was carried out in May 2019 with ethical licensing numbered 509/UN6.KEP/EC/ 2019. Data were analyzed using item analysis. The results showed that there was 32% did not get IMD or early initiation of breastfeeding, 84% did not get exclusive breastfeeding, 46% was not breastfeed until the age of two years, 6% was not been given MP-ASI or weaning food at the age of 6-8 months , 34% did not meet the minimum dietary diversity (MDD), 36% did not meet the minimum meal frequency (MMF), 56% did not meet the minimum acceptable diet (MAD), and 100% consumed iron-containing foods. The conclusion of this research is that feeding practices in children at the age of 0-23 months is still less than optimal.